2006
DOI: 10.1038/sj.bjc.6603436
|View full text |Cite
|
Sign up to set email alerts
|

The role of superoxide anions in the development of distant tumour recurrence

Abstract: We hypothesise that reactive oxygen species (ROS) released from activated polymorphonuclear leucocytes during surgery play a crucial role in enhanced tumour recurrence seen after surgery. Therefore, the effect of ROS on adhesion of tumour cells to microvascular endothelium in a reproducible human in vitro model was studied. Preincubation of microvascular endothelial cells with the superoxide anion producing xanthine -xanthine oxidase complex significantly increased adhesion of the human colon carcinoma cells H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…In addition, elevated ROS was shown to trigger ECs apoptosis that resulted in the loss of vascular barrier integrity. Application of anti-oxidants may abrogate the ROS-induced impairment of endothelial barrier (16,49). These data are intriguing and together implicate the critical role of endogenous ROS in abnormalities of tumor vessel structure and functions.…”
Section: Discussionmentioning
confidence: 82%
“…In addition, elevated ROS was shown to trigger ECs apoptosis that resulted in the loss of vascular barrier integrity. Application of anti-oxidants may abrogate the ROS-induced impairment of endothelial barrier (16,49). These data are intriguing and together implicate the critical role of endogenous ROS in abnormalities of tumor vessel structure and functions.…”
Section: Discussionmentioning
confidence: 82%
“…One of the major adhesion molecules mediating these processes is ICAM-1. It has been shown that ROS and antioxidants affect its expression in an opposed way resulting in substantial consequences for the disease course [32,33]. During tumorigenic transition in melanoma, loss of E-cadherin is accompanied by gain in N-cadherin.…”
Section: Discussionmentioning
confidence: 99%
“…There is growing evidence that surgical trauma induces ROS which have oncological implications that can facilitate tumour growth and metastasis 3 9 10. Both clinical and animal studies have shown that the trauma response associated with a laparotomy is responsible for a significant rise in ROS levels 9 59–61.…”
Section: Ros Generation In the Perioperative Settingmentioning
confidence: 99%
“…Consequently, surgical trauma creates an ROS-rich environment which allows redox signalling to occur 9 10. Emerging evidence clearly demonstrates that surgery-induced ROS is a key player in the development of local recurrence and distant metastasis following tumour resection 3 11 12.…”
Section: Introductionmentioning
confidence: 99%